Investigating the Self‐Thinning Rule in Plantation Forests: Analyzing the Relationship Between the Basal Area and Height Growth in Southern China - Shisheng Long; Xuefeng He; Siqi Zeng; Huashun Xiao (Ecology and Evolution)
ABSTRACT The self‐thinning rule in forest stands is fundamental to the development of density management strategies, as it determines the maximum stand density achievable for a given tree size. Accurate modeling of the maximum density line is crucial, but selecting representative data points for this purpose remains a challenge. Using 18 years of data from five Cunninghamia lanceolata plantations with varying initial planting densities, this study investigated whether relationships between mean tree basal area (g) and height (H) can reveal forest developmental stages and identify when stands begin self‐thinning and reach maximum density. Our results showed a significant linear relationship (p < 0.05) between g and H after self‐thinning was established, supporting the presence of self‐regulatory growth mechanisms. These findings enabled the development of a novel sample selection method for constructing more accurate maximum density line models, outperforming traditional methods that rely on arbitrary thresholds. Additionally, we derived formulas to describe total stand basal area (G1.0) during different growth stages, revealing positive correlations with mean height during early growth and negative correlations with mean diameter during self‐thinning. This research advances the understanding of self‐thinning dynamics and provides practical tools for improving density management in plantation forestry.